An integrated process for the removal of Cd and U from wet phosphoric acid - Ortiz I.; Urtiaga A .M.; Galán B.; Kabay N.; Demircioglu M.; Gizli N.; Yuksel M.; Saglam M. (Coastal zone management in the Mediterranean region, 2002)
In this work, an integrated process based on the application of two membrane technologies far the selective recovery of the Uranium and the Cadmium contained in wet phosphoric acid is presented. The process is based an the removal of U by ion exchange using the Purolite S940 resin as an exchange resin followed by the selective removal of Cd by means of membrane assisted solvent extraction with Aliquat 336 as selective extractant. Working with acidic solutions containing initially 200 mg/I of U and 50 mg/I of Cd, the viability of the process for reduction of the U and Cd concentration below 2 mg/l has been confirmed and a simplified flow diagram of the integrated process far the removal of U and Cd from wet phosphoric acid, specifying inlet and outlet concentrations and the values of the design parameters is included.